Impact of gold nanoparticles on low-voltage operating GaN ultraviolet photodetector - (:unkn) unknown (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2020)
We report, in this study, the impact of gold nanoparticles on low-voltage operating GaN ultraviolet (UV) photodetector through parameters such as detectivity, responsivity, repeatability, stability, and photo-to-dark current ratios. These studies revealed prominent increases in detectivity and responsivity of the device due to Au nanoparticle application, thus allowing it to detect weaker signals and obtain higher on/off current ratios. After the application of different quantities of Au nanoparticles to the device surface, the investigated photoelectric properties were enhanced reaching a peak detectivity of 1.09 x 10(11) Jones and a photo- to-dark current ratio of 486 at 2-V bias. Moreover, the photocurrent increased by two-fold (from 35.3 to 70.6 nA) at a low bias of 0.5 V following the application of the Au nanoparticles to the device surface. The modified GaN photodetector with a remarkable detectivity offers solutions toward improving detectivity of UV photodetectors. In consequence, having established such prosperous properties under relatively low-voltage levels with this practical and cost-effective fabrication route provides a good approach toward a wide range of UVoptoelectronic devices. (c) 2020 Society of PhotoOptical Instrumentation Engineers (SPIE)
Keywords: GaN-ultraviolet photodetector; surface-plasmon resonance effect; Au nanoparticles; high-detectivity; UV PHOTODETECTORS; HIGH-SPEED; ENHANCEMENT; DETECTORS